A Study on Problems and Malpractices Emerge during Examination of Grade 5 and Grade 8 Students in Punjab, Pakistan - Muhammad Shehzad, Ashiq Hussain Dogar (PJE, 2023)
This research was designed to explore the problems and malpractices emerge during examinations of grade 5 and grade 8 students in Punjab. It was qualitative descriptive research based on survey design in nature. Data was collected from 24 heads of Examination Cluster Centers via semi-structure interview protocol who were selected by applying simple random sampling technique.